A safety detection and protection system for power tools - SHISHEGAR, AHMAD R; SIWEK, THOMAS R; PIERGA, WOJCIECH T (2009)
A detection system for detecting a dangerous condition for an operator using a power tool of the type which has an exposed blade (26) relative to a work surface (28) and a protection system for minimizing, if not eliminating the possibility of a user being injured by contacting the blade. In the present invention, a proximity detection system is capable of detecting the presence of a user near the blade of a table saw and a protection system that can retract the blade below the work surface of the table saw and wherein the blade is electrically isolated from said arbor, drive motor output shaft and frame structure, so that an excitation field can be applied to said blade (26).